Analogy, polarity and morality in Scythian Hippake: Reflections on Herodotus, Histories 4.2 - Braund, D. (Археологія і давня історія України, 2018)
This paper has two principal purposes. First, in section 1, I offer some very general points about how we may best understand Greek treatments of Scythian themes. It is argued that the tendency to stress the difference (even polarity) between Greeks and Scythians should be balanced and at least contextualised by consideration of similarities and analogies too. In the second part, it is argued in detail that the milking of horses was by no means strange to Greeks, even though Greeks made much less use of horse milk, and preferred to consume it in liquid form and not as cheese (hippake).